The economics of permissible WTO retaliation - Chad P. Bown; Michele Ruta (World Trade Organization (WTO), 2008)
We examine how theoretical and quantitative economic analysis has and can be used in this stage of the DSU process. First, we identify, characterize, and categorize the major classes of disputes e.g., those affecting import protection versus export promotion and use the Bagwell and Staiger interpretation of the WTO principle of reciprocity to provide a theoretical framework that arbitrators can use to identify the maximum level of retaliatory countermeasures. Second, we allocate each of the ten DSU arbitrations that have taken place thus far into one of these categories and compare the arbitrators' actual approach with the theory. Third, we use this framework to identify three crucial elements to the arbitrators' decision-making process for each case: i) the formula that they decide to adopt for identifying appropriate countermeasures, ii) their political-legal-economic decision on a WTO-consistent counterfactual to use to implement the formula, and iii) the quantitative methods they use to necessarily construct the (unobserved) WTO-consistent counterfactual. We examine not only the arbitrations that have taken place thus far, but our approach also illustrates a template for many additional types of arbitrations likely to take place under the DSU. Finally, in the disputes in which this reciprocity approach has not been used, we identify procedural difficulties that arbitrators confront thus highlighting the constraints that hinder their use of economic analysis in practice.
Keywords: F13; F51; K33; 330; WTO; DSU; arbitrations; reciprocity; retaliation; market access; terms-of-trade externality; Internationale Schiedsgerichtsbarkeit; Retorsionsmaßnahme; WTO-Regeln